СУЧАСНІ ТЕНДЕНЦІЇ ВОКАЛЬНОЇ ПІДГОТОВКИ МАЙБУТНЬОГО ВЧИТЕЛЯ-МУЗИКАНТА (Pedagogy of Higher and Secondary Education, 2012)
У статті розглядаються сучасні тенденції дослідження мети, змісту складу, завдань, методів вокальної підготовки майбутніх педагогів-музикантів, яка є важливим компонентом фахової підготовки студентів у вищих навчальних закладах музично-педагогічного спрямування. Ключові слова: вокальна підготовка, вокальна компетентність, постановка голосу, методи вокальної підготовки. Тhe main lines of research intention, content, structure, tasks, methods of future teachers-musicians vocal training are considered in this article, which is an important component of professional training students in higher education institutions of the musical-pedagogical direction. Key words: vocal training, vocal competence, voice development, vocal training methods.
Keywords: vocal training; vocal competence; voice development; vocal training methods